Design of an Experimental System for the Assessment of the Drug Loss in Drug-Coated Balloons Due to Washing Off During Tracking - Dimitrios Zantzas; Elena Bianchi; Francesca Berti; Mohammad Akrami-Hasan-Kohal; Tahmer Sharkawi; Giancarlo Pennati (Designs)
Drug-coated balloons (DCBs) are designed to deliver an anti-proliferative drug to the stenotic vessel to combat restenosis after an angioplasty treatment. However, significant drug loss can occur during device navigation toward the lesion site, thus reducing the delivery efficiency and increasing the off-target drug loss. In this framework, this study aimed to design a novel in vitro setup to estimate the drug loss due to blood flow–coating interaction during tracking. The system consists of a millifluidic chamber, able to host small drug-coated flat patches representative of DCBs, connected at the inlet to a syringe pump able to provide an ad hoc flow and, at the outlet, to a vial collecting the testing fluid with possible drug removed from the specimen. Unlike other studies, the device presented here uniquely evaluates flow-related drug loss from smaller-scale DCB samples, making it a precise, easy-to-use, and efficient assessment tool. In order to define proper boundary conditions for these washing off tests, computational fluid dynamics (CFD) models of a DCB in an idealized vessel were developed to estimate the wall shear stresses (WSSs) experienced in vivo by the device when inserted into leg arteries. From these simulations, different target WSSs were identified as of interest to be replicated in the in vitro setup. A combined analytical–CFD approach was followed to design the testing system and set the flow rates to be imposed to generate the desired WSSs. Finally, a proof-of-concept study was performed by testing eight coated flat specimens and analyzing drug content via high-performance liquid chromatography (HPLC). Results indicated different amounts of drug loss according to the different imposed WSSs and confirmed the suitability of the designed system to assess the washing off resistance of different drug coatings for angioplasty balloons.